IMPLEMENTASI LOAD BALANCING DUA LINE ISP MENGGUNAKAN MIKROTIK ROUTEROS [STUDI KASUS SISTEM JARINGAN LAN DI PT. WAHANA SEMESTA BANGKA (BABEL POS)] - Arianto, Eris; Sholeh, Muhammad; Nurnawati, Erna Kumalasari (Jurnal Jarkom, 2014)
ABSTRACTNeed for Internet access currently very high, either to find information, article and latest knowledge. Lots establishments have integrated the Internet into daily activities of environmental workplace. This it expected that the company can facilitate activities with ease. PT. Universe rides Bangka (Babylon Pos) is an establishments that stir of newspapers in the field of. On problem above, designed a network capable handling solid connection problems and slow, and used mikrotik for load balancing, load balancing with the solid lines will be balanced. Therefore arising solutions using two ISP and make the mikrotik load balancer. Mechanism that will mark the package mikrotik access internet, select a line which will be passed ISP and ISP equalize load. Based system development methods are used, namely Network Development Life Cycle (NDLC), before determine load balancing method, author conducted an analysis of network conditions be applicable in Babel Pos. Selection of PCC load balancing method because it meets criteria because it can increase speed the connection and share the burden on both the gateway to prevent overload. Then authors also Implementing techniques fail over, which is where if one gateway connection was lost, the other gateways will be automatically backups and sustains all network traffic.Â Keywords: Double internet connection, Load Balancing, Mikrotik